RANCANG BANGUN MONITORING DEBIT AIR PDAM RUMAH TANGGA BERBASIS INTERNET OF THINGS (IOT) - Roza, Yuni; KH, Musliadi; Pernando, Yonky; Syafrinal, Ilwan; Kaharuddin, Kaharuddin (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
Indonesia is an archipelagic country that has a tropical climate. This country is also famous for its wealth in various natural resources, one of which is water. Water is a source of human needs which is important for survival and is used for daily needs such as consumption, bathing, washing and others. As a society, of course you have to pay attention to the quality in the use of water, for this reason the government provides PDAM (Regional Drinking Water Company). In using PDAM facilities, especially in the South Sulawesi area, Mamuju Regency, it is necessary to monitor the amount of usage every month. The meter display is still analog and the amount of tariff or bill that must be paid by the public is not yet listed. The amount of bills that must be paid is the result of recording by PDAM officers who come every month. With this, tools are needed to monitor usage and the amount of bills that will be paid by the Internet of Things (IoT) based community. With this IoT-based control tool, people can see the amount of water used and the tariff they have to pay each month.